Stability of jabuticaba flakes obtained by drum drying with cassava starch as additive - Nunes, Larissa Peixoto; et. al. (2021)
The stability of jabuticaba flakes produced by drum drying using cassava starch as additive was evaluated. Sorption isotherms at 25 ºC were determined. Samples were stored under controlled conditions (relative humidity = 60%, temperature = 20, 25 and 35 ºC) for until 235 days. The anthocyanin content and color parameters (L*, a* and b*) were monitored. GAB model led to the best adjustment of sorption isotherm, with a monolayer moisture value of 0.1596 g water/g dry basis. The visual observations did not point out agglomerations and darkening at aw values higher than 0.33 at 25 ºC, which can be considered the critical point. The degradation of anthocyanin and color parameters followed first and zero-order kinetic model, respectively. The half-life times (630 to 1450 days) showed good stability at 25 ºC, while the temperature acceleration coefficient (2.2 ≤ Q10 ≤ 3.2) and activation energy (15 ≤ Ea ≤ 19 kcal/mol) values demonstrated a high-temperature sensitivity.